PENGARUH PENDIDIKAN ORANG TUA TERHADAP MOTIVASI BELAJAR SISWA DALAM MATA PELAJARAN AQIDAH AKHLAQ DI MA PLUS BURHANUL HIDAYAH KREMBUNG SIDOARJO - Mohammad Ainur Rozi; Fathurrahman Alfa; Kukuh Santoso (Vicratina : Jurnal Ilmiah Keagamaan, 2021)
The education of a child gets brilliant achievements with parents who only graduate from elementary school while children whose parents are highly educated are not even cared for in terms of education, it is because of the attention of parents and the motivations given to a child, as is the case in MA plus Burhanul Hidayah. The focus of the research discusses how the level of parents, how to motivate parents, and how the influence of parental education on students' motivation. To achieve this goal, the researcher used a descriptive quantitative approach. Researchers conducted observations, interviews, and distributed questionnaires. Here the researcher will collect data followed by scoring to find the value of the distribution of the questionnaire. Validation and reliability tests are used to determine whether there is a correlation between variables X and Y. Finally, to determine whether the regression coefficient is significant or not (in the sense that the X variable has or does not affect the Y variable), it is possible to test the hypothesis by comparing the significant value of 0.05. If the significant value is less than 0.05 then there is an effect between the X variable on the Y variable and vice versa.